1 The cathepsin-L inhibitor CAA0225 protects against myocardial ischaemia-reperfusion injury. (17th November 2015) - He, W; McCarroll, CS; Nather, K; Elliott, EBA; Nicklin, SA; Loughrey, CM
Abstract : Ischaemia-reperfusion (IR) injury contributes to the cardiac damage following myocardial infarction and paradoxically reduces the benefits of reperfusion therapy. In patients with ischaemic heart disease, cathepsin-L is elevated in the serum and correlates with disease severity. Our data demonstrate that cathepsin-L released from ex vivo rat hearts after ischaemia, and the cathepsin-L inhibitor CAA0225 improves cardiac function during ischaemia-reperfusion ex vivo . However, the effects of the CAA0225 in in vivo hearts during ischaemia-reperfusion are unknown. We hypothesised that using CAA0225 in an in vivo mouse model of ischaemia-reperfusion would identify the role cathepsin-L plays during ischaemia-reperfusion. Ischaemia-reperfusion injury was induced by 45 min temporary coronary artery ligation and CAA0225 was given by intra-venous injection during ischaemia before reperfusion. Double-dye staining demonstrated no difference in area at risk between groups whereas CAA0225 significantly reduced infarct size to 73% of control. Echocardiography demonstrated significantly preserved left ventricular fractional shortening at 2 wk and 4 wk post-IR in CAA0225 treated mice compared with control mice. PV loop measurements demonstrated CAA0225 treated mice had higher developed pressure than control mice at 2 weeks post-IR. Ex vivo isolated rat cardiomyocytes demonstrated that ischemia-reperfusion increased calcium influx through L-type calcium channels, reduced sarcolemmal NCX extrusion and SERCA activity. While CAA0225 treatment normalised the abnormalities of intracellular calcium handling parameters back to control thus reducing calcium waves following ischaemia-reperfusion. These data demonstrate for the first time that CAA0225 protects against ischaemia-reperfusion injury in mice and the mechanism relates to the normalisation of abnormal calcium handling following ischaemia-reperfusion injury.